The Role of Family in the Socio-Economic Resilience of Former Drug Dealers in Aceh - Fakhrurrazi , Fakhrurrazi; Yunanda, Rizki; Nirzalin , Nirzalin; Zawil Kiram, Muhammad (Universitas Negeri Semarang, 2025)
This study examines the role of families in the socio-economic resilience of former drug dealers in Ujong Pacu, Lhokseumawe city. In many cases, former drug dealers return to drug dealers after they are released from prison. However, in Ujong Pachu, former drug dealers are able to survive not returning to become drug dealers even though they often receive persuasive invitations and threats to return to being active in drug networks. This study aims to find the role of families in the socio-economic resilience of ex-drug dealers in Ujong Pacu, which can be used as a reference for the transformation process of ex-drug dealers in other regions, especially in Indonesia. Data collection was carried out through observation, in-depth interviews, focus group discussions (FGD) and the use of documents. The results of this study show that since 2015, collective efforts in Gampong Ujong Pacu to eradicate drugs through collaboration between community leaders, Teungku Dayah, local government and family roles have succeeded in creating a safer environment by breaking the chain of drug spread and supporting social recovery. Rehabilitation programs, job provision, and emotional support play an important role in the integration of former dealers into society. However, challenges remain, especially in terms of financial stability and social support for individuals who are still struggling, demonstrating the need for a more holistic and sustainable approach.